Aspiration as a late complication after accelerated versus conventional radiotherapy in patients with head and neck cancer. (3rd March 2016) - Lindblom, Ulrika; Nilsson, Per; Gärskog, Ola; Kjellen, Elisabeth; Laurell, Göran; Wahlberg, Peter; Zackrisson, Björn; Levring Jäghagen, Eva
Abstract: Conclusion Neck dissection after radiotherapy increased the risk of aspiration as a late effect in a sub-sample of patients treated for head and neck cancer in the ARTSCAN study. Patients treated with accelerated fractionation (AF) developed aspiration, with or without coughing, more frequently than patients treated with conventional fractionation (CF).Objectives A long-term follow-up study was conducted to determine the frequency of aspiration as a late effect in patients with head and neck cancer treated with AF or CF.Method One-hundred and eight patients were recruited from two centres of the Swedish multi-centre study, ARTSCAN, where AF and CF were compared. Patients with positive lymph nodes were treated with neck dissection after completing radiotherapy. The follow-up was performed at a median of 65 months after initiation of radiotherapy and included an ENT and a videofluoroscopic examination.Results Aspiration was found in 51/108 (47%) and silent aspiration in 34/96 (35%) patients. Neck dissection ( n  = 47 patients) was significantly associated with both aspiration and silent aspiration. Aspiration was more common among patients treated with AF (34/61; 56%) compared to CF (17/47; 36%; p  = 0.053). Silent aspiration was also more common after AF (24/54; 44%) than after CF (10/42; 24%; p  = 0.052).